2018
DOI: 10.1002/rmb2.12080
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of high‐dose i.v. immunoglobulin therapy for pregnant women with aspirin–heparin‐resistant secondary antiphospholipid syndrome

Abstract: PurposeThis study aimed to assess the efficacy of high‐dose i.v. immunoglobulin (HIVIg) therapy in pregnant women with antiphospholipid syndrome (APS) secondary to systemic lupus erythematosus with a history of pregnancy failure, despite receiving low‐dose aspirin plus unfractionated heparin therapy, of which condition being designated as “aspirin–heparin‐resistant APS” (AHRAPS).MethodsThe HIVIg therapy (20 g/d, 5 days) was performed for the pregnancies of five women with AHRAPS.ResultsFive of the eight pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Lefkou et al demonstrated that in women with antiphospholipid syndrome and preeclampsia or intrauterine growth restriction (IUGR), the administration of 20 mg of pravastatin led to improved pregnancy outcomes and fetal health [59][60][61]. Furthermore, the efficacy of high-dose intravenous immunoglobulin therapy for pregnant women with aspirin-heparin-resistant secondary antiphospholipid syndrome was also evaluated [62]. Therapeutic options are presented in Table 3.…”
Section: Treatment Options In Apsmentioning
confidence: 99%
“…Lefkou et al demonstrated that in women with antiphospholipid syndrome and preeclampsia or intrauterine growth restriction (IUGR), the administration of 20 mg of pravastatin led to improved pregnancy outcomes and fetal health [59][60][61]. Furthermore, the efficacy of high-dose intravenous immunoglobulin therapy for pregnant women with aspirin-heparin-resistant secondary antiphospholipid syndrome was also evaluated [62]. Therapeutic options are presented in Table 3.…”
Section: Treatment Options In Apsmentioning
confidence: 99%